Growth, Yield and Quality Attributes of Determinate Tomato Genotypes in Parwanipur, Bara of Nepal - Chaudhary, Jeet Narayan; Srivastava, Arvind; Sharma, Moha Dutta; Gautam, Ishwori Prasad (Agronomy Journal of Nepal, 2024)
With the aim of identifying suitable open pollinated determinate tomato genotypes, investigation was carried out at Directorate of Agricultural Research (DoAR), Parwanipur in two consecutive winter seasons of 2020/21 and 2021/22. Experiment was laid out in randomized complete block design (RCBD) with 16 treatments and replicated thrice. Crop geometry was maintained 75×60 cm and fertilizers and manure was applied at the rate of 200:150:120 kg N: P2O5:K2O kg + 20 tons FYM per hectare. Analysis of results showed significant variation in yield and yield attributing characters among genotypes. The maximum plant height (75.67 cm) was recorded on genotypes AVTO 0301.The genotypes AVTO 1716 and AVTO 0301 showed significantly earlier to 50% flowering (45 days) while AVTO 1711 recorded shortest days to first harvest (81 days). The highest plant vigour (5 scales) showed by AVTO 1712, AVTO 0302 and Pusa Ruby check variety. The maximum fruit diameter (7.52 cm), length (6.54 cm) and fruit weight (49.9 g) recorded on genotype AVTO 1711. The highest number of fruits/ plant (56.7) and marketable yield (58.08 t ha-1) was recorded in AVTO 1610 and AVTO 1711 respectively. The genotype AVTO 1712 showed the highest firmness (1.92 kg cm-2) and Vitamin C (59.36 mg/ 100 g). The maximum pericarp thickness of fruits (7.43 mm) obtained on AVTO 1610. The genotype Pusa Ruby showed the maximum total soluble solid (5.6 Obrix) and Titratable acid 0.75 %. Similarly, the highest colorimetric value of a* (12.62) was recorded on Pusa Ruby and the highest value of b* (19.37) was found on AVTO 1713 while the highest value of L* (30.56) was observed on AVTO 171.  Considering the overall performance, genotypes AVTO 1711, AVTO 1702 and AVTO 1712 were performed better in terms of the highest yield and other horticultural traits.